2018
DOI: 10.17116/otorino201883377
|View full text |Cite
|
Sign up to set email alerts
|

The patulous Eustachian tube syndrome: the current state-of-the-art and an original clinical observation. Second communication

Abstract: The choice of the treatment strategy for the patients presenting with the patulous Eustachian tube syndrome constitutes a serious challenge for an otorhinolaryngologist. Despite the considerable progress achieved during the past years in the development of modern pharmacotherapy and functional endoscopic surgery, the specialists often encounter difficulties in the management of the patients suffering from this disease. The present article (continuing the previous communication) contains information concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In general, the ET plays an important role in equalization, oxygenation, and drainage of the tympanic cavity in the middle ear; its structure provides a controlled air exchange in the tympanic cavity or provides an outlet for mucus and other fluid from the middle ear to the nasopharynx. 23 The ET is composed of bone, cartilage, and connective tissue. Based on data from 10 cadavers, Brown et al 24 reported the mean distance from the nasopharynx to the ET genu was 23 mm (SD 5 mm), the mean distance from the ET genu to the anterior aspect of the tympanic membrane was 24 mm (SD 3 mm), and the mean total ET length was 47 mm (SD 4 mm).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the ET plays an important role in equalization, oxygenation, and drainage of the tympanic cavity in the middle ear; its structure provides a controlled air exchange in the tympanic cavity or provides an outlet for mucus and other fluid from the middle ear to the nasopharynx. 23 The ET is composed of bone, cartilage, and connective tissue. Based on data from 10 cadavers, Brown et al 24 reported the mean distance from the nasopharynx to the ET genu was 23 mm (SD 5 mm), the mean distance from the ET genu to the anterior aspect of the tympanic membrane was 24 mm (SD 3 mm), and the mean total ET length was 47 mm (SD 4 mm).…”
Section: Discussionmentioning
confidence: 99%